Aptamer tethered bio-responsive mesoporous silica nanoparticles for efficient targeted delivery of paclitaxel to treat ovarian cancer cells - Salve, Rajesh; Kumar, Pramod; Chaudhari, Bhushan P.; Gajbhiye, Virendra (Journal of Pharmaceutical Sciences, 2023)
Ovarian cancer is the leading cause of cancer deaths in female patients. The current therapeutics in ovarian cancer are limited and inefficient in curing the disease. To tackle this, we have synthesized tetrasulfide deriv-ative of silica doped, biodegradable, glutathione-responsive targeted mesoporous silica nanoparticles modi-fied with heterobifunctional polyethylene glycol as a linker and mucin-1 aptamer for triggered paclitaxel delivery to the ovarian cancer cells. Degradable mesoporous silica nanoparticles were synthesized by a modi-fied sol-gel method with tetraethyl orthosilicate and Bis (triethoxysilylpropyl) tetrasulfide. The degradable mesoporous silica nanoparticles were characterized by dynamic light scattering, Fourier-transform infrared spectroscopy, Scanning electron microscopy and Transmission electron microscopy. The degradable mesopo-rous silica nanoparticles had good paclitaxel encapsulation efficiency and glutathione-responsive paclitaxel release ability. The glutathione utilization assay and visual destruction observed within 10 days in transmis-sion electron microscopy images confirmed the degradation of the mesoporous silica nanoparticles in the tumor cell environment. The targeted degradable mesoporous silica nanoparticles were efficiently taken up by ovarian cancer cell lines OVACAR-3 and PA-1. The cytotoxicity of bare mesoporous silica nanoparticles evaluated on NIH-3T3 cell line showed good biocompatibility (>90% cell viability). Significant toxicity on OVACAR-3 (IC50 25.66 nM) and PA-1 (IC50 42.93 nM) cell lines was observed when treated with paclitaxel-loaded targeted degradable mesoporous silica nanoparticles. Results of this study demonstrated that mucin-1 targeted, glutathione-responsive mesoporous silica nanoparticles loaded with paclitaxel had a significant antitumor effect on ovarian cancer cells. All these findings demonstrated that developed nano-formulation could be suitable for ovarian cancer treatment. & COPY; 2023 American Pharmacists Association. Published by Elsevier Inc. All rights reserved.
Keywords: Degradable; GSH; Mesoporous silica nanoparticles; Mucin-1; Ovarian cancer; Paclitaxel; Stimuli-responsive